Mythological influence on ancient pottery formations of models (the mother goddess producing offspring) - Alia Mohsen Abboud (مجلة فنون البصرة)
The study of mythological influences in ancient pottery formation, corresponding to the models of what is known as (the mother who produces offspring), is of clear importance, in terms of investigating the sufficient mythological ideas in the pottery formation models, as it occupied an important place in the course of ancient global ceramic formation, given that it has a strong relationship with social thought, with all its historical, environmental, mythological, and ideological specificities, taking into consideration the nature of the pottery formations, representing the model of (the mother who produces offspring), and what it carries of expressive and suggestive connotations related to mythology, which gave it a special character, as it enjoyed the specificity of the formal composition, in addition to the techniques of display in the ancient process of pride and coloring.